Exchange rates and the global transmission of equity market shocks - Javier Ojea-Ferreiro; Juan Carlos Reboredo (European Commission, 2021)
We assess the role played by exchange rates in buffering or amplifying the propagation of shocks across international equity markets. Using copula functions we model the joint dependence between exchange rates and two global equity markets and, from a copula framework, we obtain the conditional expectation and measure the exchange rate contribution to shock propagation between those equity markets. Our estimates for emerging Latin American economies (Argentina, Brazil, Chile and Mexico) and two developed markets (Europe and the USA) document the following: (a) the contribution of exchange rates to the transmission of equity shocks is time varying and asymmetric and differs across countries; and (b) exchange rates diversify shocks from abroad for investors based in emerging economies (particularly Brazil, Chile and Mexico) and echo the effect of shocks from abroad for investors based in developed markets. This evidence has implications for international investors in terms of portfolio and risk management decisions.
Keywords: C58; F31; G15; 330; Exchange rates; International equity markets; Copulas; Expected shortfall